619 Findings regarding the relationship between parenting styles and sociodemographic parameters in families having children with cerebral palsy (Balneo and PRM Research Journal, 2024)
The ability of parents to provide the correct conditions for healthy development, support, and prepare children for maturity determines a child's physical, cognitive, emotional, and social growth. According to the literature, numerous factors influence parenting styles. This study aimed to investigate, using sociodemographic parameters, whether the parenting styles of fathers and mothers in families with disabled children differ from one another. The research was conducted at the "Dr. N. Robănescu" National Center of Neurorehabilitation for Children. It included 71 parents of children with cerebral palsy questioned using the Parenting Styles Questionnaire (PSQ), a Romanian-adapted version. Of the five examined parenting styles, the authoritative approach was the most prevalent. The results show a statistically significant difference in the means of uninvolved parenting styles between urban mothers and fathers, a statistically significant difference in the means of authoritarian, authoritative, and uninvolved parenting styles between married mothers and fathers, a statistically significant difference in authoritative parenting style between different education levels; there, was no significant difference in parenting style between different income levels; and a considerable difference in permissive parenting between various employment statuses. This research suggests that some sociodemographic parameters had impact on the parenting styles of our study group. Keywords: parenting style; cerebral palsy; sociodemographic parameters; children